Molecular electronic spin qubits from a spin-frustrated trinuclear copper complex. Issue 92 (10th October 2018) - Kintzel, Benjamin; Böhme, Michael; Liu, Junjie; Burkhardt, Anja; Mrozek, Jakub; Buchholz, Axel; Ardavan, Arzhang; Plass, Winfried
Abstract : The trinuclear copper(ii ) complex [Cu3 (saltag)(py)6 ]ClO4 (H5 saltag = tris(2-hydroxybenzylidene)triaminoguanidine) was synthesized and characterized by experimental as well as theoretical methods. Abstract : The trinuclear copper(ii ) complex [Cu3 (saltag)(py)6 ]ClO4 (H5 saltag = tris(2-hydroxybenzylidene)triaminoguanidine) was synthesized and characterized by experimental as well as theoretical methods. This complex exhibits a strong antiferromagnetic coupling ( J = −298 cm −1 ) between the copper(ii ) ions, mediated by the N–N diazine bridges of the tritopic ligand, leading to a spin-frustrated system. This compound shows a T 2 coherence time of 340 ns in frozen pyridine solution, which extends to 591 ns by changing the solvent to pyridine-d5 . Hence, the presented compound is a promising candidate as a building block for molecular spintronics.